Francisco Doratioto, Maldita Guerra. Nueva historia de la guerra del Paraguay, Buenos Aires, Emecé, 2004, 640 pp - García Belsunce, César A. (2005)
Fil: García Belsunce, César A. Academia Nacional de la Historia de la República Argentina; Argentina